The Design of the Pedagogical Competencies in the Structure of Professional Preparation of Teachers (Journal of Educational Sciences, 2016)
In the article the authors consider the question of the training of teachers of higher education at University level. The most important task of professional education – designing professional competences, and through this and the personality of the future specialist. This approach assumes theunity of the personal and professional qualities: professional autonomy, professional mobility, educational competence, professionalism, responsibility, etc. Submitted to the program target coordinates and the directions of the methodical competence of teacher of high school. Designed themodel of formation of professional competence of University teachers. In the model presented 100 valuation parameters of quality of activity of teacher of higher school. They are grouped in didactic, organizational, gnostic, educational, personal-individual, artistic and other. The authorsconclude that for the formation of pedagogical competence of particular importance is the personal component.
Keywords: University education; high school teacher; the identity specialist; design culture; competence; pedagogical competence; professional independence; professional mobility; professionalism